Reference values for cardiopulmonary exercise testing in healthy subjects - an updated systematic review - Takken, T.; Mylius, C.F.; Paap, D.; Broeders, W.; Hulzebos, H.J.; Van Brussel, M.; Bongers, B.C. (Expert review of cardiovascular therapy, 2019)
Introduction: Reference values for cardiopulmonary exercise testing (CPET) parameters provide the comparative basis for answering important questions concerning the normalcy of exercise responses in patients, and significantly impacts the clinical decision-making process. Areas covered: The aim of this study was to provide an updated systematic review of the literature on reference values for CPET parameters in healthy subjects across the life span. A systematic search in MEDLINE, Embase, and PEDro databases were performed for articles describing reference values for CPET published between March 2014 and February 2019. Expert opinion: Compared to the review published in 2014, more data have been published in the last five years compared to the 35 years before. However, there is still a lot of progress to be made. Quality can be further improved by performing a power analysis, a good quality assurance of equipment and methodologies, and by validating the developed reference equation in an independent (sub)sample. Methodological quality of future studies can be further improved by measuring and reporting the level of physical activity, by reporting values for different racial groups within a cohort as well as by the exclusion of smokers in the sample studied. Normal reference ranges should be well defined in consensus statements.